Neuroanatomical changes seen in MRI in patients with cerebral metastasized breast cancer after radiotherapy - Reibelt, Antonia; Mayinger, Michael; Borm, Kai J.; Combs, Stephanie E.; Duma, Marciana N. (Tumori, 2022)
Purpose: To quantify neuroanatomical changes using magnetic resonance imaging (MRI) in patients with cerebral metastasized breast cancer after brain radiotherapy (RT). Methods: Fifteen patients with breast cancer with brain metastases who underwent whole brain RT (WBR), radiosurgery (RS), and/or hypofractionated stereotactic treatment (STX) were examined at four time points (TPs). A total of 48 MRIs were available: prior to RT (TP1), 5–8 months after RT (TP2), 9–11 months after RT (TP3), and >20 months after RT (TP4). Using automatic segmentation, 25 subcortical structures were analyzed. Patients were split into three groups: STX (receiving STX and RS), RS (receiving RS only), and WBR (receiving WBR at least once). After testing for a normal distribution for all values using the Kolmogorov-Smirnov test, a two-sided paired t test was used to analyze volumetric changes. For those values that were not normally distributed, the nonparametric Mann-Whitney test was employed. Results: The left cerebellum white matter (p = 0.028), the right pallidum (p = 0.038), and the left thalamus (p = 0.039) significantly increased at TP2 compared to TP1. The third ventricle increased at all TPs (p = 0.034–0.046). The left choroid plexus increased at TP3 (p = 0.037) compared to TP1. The left lateral ventricle increased at TP3 (p = 0.012) and TP4 (p = 0.027). Total gray matter showed a trend of volume decline in STX and WBR groups. Conclusions: These findings indicate that alterations in the volume of subcortical structures may act as a sensitive parameter when evaluating neuroanatomical changes and brain atrophy due to radiotherapy. Differences observed for patients who received STX and WBR, but not those treated with RS, need to be validated further.
CRIS-Team Scopus Importer:2023-03-08
Keywords: brain radiotherapy; cerebral metastasized breast cancer; FreeSurfer; Neuroanatomical changes